The Urgence of Writing Awig's Pararem in Increasing Community Legal Awareness in Traditional Village Pelem Gede, Tabanan - I Ketut Sukadana; Luh Putu Suryani; Ni Made Puspasutari Ujianti; I Ketut Jika; Kadek Ayu Surya Dwi Utami (Fakultas Hukum, Universitas Warmadewa, 2023)
Desa Adat is a traditional village in Bali which has been autonomous since its inception. Each Traditional Village has its own management and assets, and has the authority to make rules, known as awig-awig and/or pararem. It turns out that the program partners do not yet have pararem panyahcah awig as rules for implementing awig-awig. By providing accessible and relevant information about legal rights, responsibilities, and processes,